Hidden truth of circulating neutrophils (polymorphonuclear neutrophil) function in periodontally healthy smoker subjects - Agarwal, Chitra (J Indian Soc Periodontol, 2016)
CONTEXT: Tobacco smoking is considered to be a major risk factor associated with periodontal disease. Smoking exerts a major effect on the protective elements of the immune response, resulting in an increase in the extent and severity of periodontal destruction. AIMS: The aim of the present study was to assess viability and phagocytic function of neutrophils in circulating blood of the smokers and nonsmokers who are periodontally healthy. SETTINGS AND DESIGN: Two hundred subjects in the mean range of 20–30 years of age were included in the study population. It was a retrospective study carried out for 6 months. MATERIALS AND METHODS: Two hundred subjects were divided into four groups: 50 nonsmokers, 50 light smokers (<5 cigarettes/day), 50 moderate smokers (5–15 cigarettes/day), and 50 heavy smokers (>15 cigarettes/day). Full mouth plaque index, sulcus bleeding index, and probing depths were measured. Percentage viability of circulating neutrophils and average number of phagocytosed Candida albicans were recorded. STATISTICAL ANALYSIS USED: Means and standard deviations were calculated from data obtained within the groups. Comparison between the smokers and nonsmokers was performed by Kruskal–Wallis ANOVA analysis. Comparison between smoker groups was performed using Mann–Whitney–Wilcoxon test. RESULTS: Percentage viability of neutrophils was significantly less in heavy smokers (66.9 ± 4.0), moderate (76.6 ± 4.2), light smokers (83.1 ± 2.5) as compared to nonsmokers (92.3 ± 2.6) (P < 0.01). The ability of neutrophils to phagocytose, i.e., mean particle number was significantly less in light smokers (3.5 ± 0.5), moderate smokers (2.3 ± 0.5), and heavy smokers (1.4 ± 0.5) compared to nonsmokers (4.9 ± 0.7) (P < 0.01) with evidence of dose-response effect. CONCLUSIONS: Smoking significantly affects neutrophils viability and phagocytic function in periodontally healthy population.